2020
DOI: 10.7554/elife.58765
|View full text |Cite
|
Sign up to set email alerts
|

REV-ERBα mediates complement expression and diurnal regulation of microglial synaptic phagocytosis

Abstract: The circadian clock regulates various aspects of brain health including microglial and astrocyte activation. Here we report that deletion of the master clock protein BMAL1 in mice robustly increases expression of complement genes, including C4b and C3, in the hippocampus. BMAL1 regulates expression of the transcriptional repressor REV-ERBa, and deletion of REV-ERBa causes increased expression of C4b transcript in neurons and astrocytes as well as C3 protein primarily in astrocytes. REV-ERBa deletion increased … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 52 publications
5
43
0
Order By: Relevance
“…REV-ERBα-deleted microglial cells showed decreased microglial branching and increased CD68, IL-6, CCl2, and TNF-α expressions [60]. Moreover, REV-ERBα-deficient mice showed increased microglial phagocytosis of synapses in the CA3 region of the hippocampus [29]. Similarly, genetic or pharmacological suppression of REV-ERBα in microglial cells showed decreased uptake and clearance of Aβ [61].…”
Section: Alteration Of Clock Genes Changes the Microglial Phenotypementioning
confidence: 97%
See 1 more Smart Citation
“…REV-ERBα-deleted microglial cells showed decreased microglial branching and increased CD68, IL-6, CCl2, and TNF-α expressions [60]. Moreover, REV-ERBα-deficient mice showed increased microglial phagocytosis of synapses in the CA3 region of the hippocampus [29]. Similarly, genetic or pharmacological suppression of REV-ERBα in microglial cells showed decreased uptake and clearance of Aβ [61].…”
Section: Alteration Of Clock Genes Changes the Microglial Phenotypementioning
confidence: 97%
“…Over the last decade, microglial interactions with synapses were shown to play crucial roles in the formation, maintenance, and elimination of synapses, and to be involved in neuronal plasticity for learning, memory, and adaptation to enriched or stressful environments. Beyond immunosurveillance, microglia showed diurnal rhythmicity with synapse phagocytosis for maintaining the homeostasis of synaptic strength [12,28,29]. In a time-lapse imaging study on dexmedetomidine (DEX)-sedated mice, microglia showed greater motility and made more frequent contacts with motile cortical dendritic spines [25].…”
Section: Diurnal Rhythmicity In Microglial Interactions With Neurons and Neuronal Elementsmentioning
confidence: 99%
“…Transcripts of pro-inflammatory cytokines- Il1b , Il6 , and Tnfa , also show a time-of-day difference in microglia, with elevated expression during the light phase ( Fonken et al., 2015 ; Wang et al., 2020 ). Additionally, microglial phagocytosis exhibits time-of-day variation ( Choudhury et al., 2020 ; Griffin et al., 2020 ). Disruption of the circadian function of microglia may sensitize hippocampal inflammatory response in aged rats ( Fonken et al., 2016 ).…”
Section: Effect Of Circadian Clock On Neurodegenerationmentioning
confidence: 99%
“…In addition, both global Bmal1 knockout and global Rev-erba knockout increase the expression of complement-related genes in the hippocampus; an enhanced transcript of C4b is also observed in the cerebral cortex of neuron and astrocyte Bmal1 knockout mice ( Lananna et al., 2018 ; Griffin et al., 2019b ; Griffin et al., 2020 ). Elevated expression of C4b has also been seen in the neuron-specific Bmal1 knockout and astrocyte-specific Bmal1 knockout mice, but not in microglia-specific Bmal1 knockout mice ( Griffin et al., 2020 ).…”
Section: Effect Of Circadian Clock On Neurodegenerationmentioning
confidence: 99%
See 1 more Smart Citation